Creep and shrinkage deformation of frp sheet strengthened reinforced concrete beam - Khairul Anwar, Zukiflee (Universiti Malaysia Sarawak (UNIMAS), 2010)
Innovation in enhancing the performance of concrete structure members had been introduced using externally bonded fiber reinforced polymer sheet. This technique has been reported effective in enhancing the strength of bridge structure and beam. The fiber reinforced polymer (FRP) strip is attached to the beam with an adhesive. The purpose of this research was to investigate the flexural behavior and long-term performance in terms of deflection taking on the effect of creep and shrinkage effect for reinforced concrete beam strengthened with fiber reinforced polymer sheet. The behavior of the beams was studied through their load-deflection characteristic and time-deflection characteristics. In addition, the tension stiffening model was introduced to determine the accurate stiffness of the cracked section. In theoretical study, a comprehensive analytical method is proposed to calculate the short term and long term deflection of both normal RC beam and RC beam strengthened with FRP sheet. The theoretical prediction is compared it with experimental results. In the experimental study, three normal RC beam will act as a control beams (reinforced concrete beam without FRP sheet attached) where one RC beam is tested for the short term flexural behavior under sustained load and another two is tested for the long term behavior under uniformly distributed load. The results indicated that the strengthened beam performed better than the control beams and analytical method used give an approximate result to the experimental analysis.